The average rate of change is given by (∆Y)/(∆X), where ∆Y is the difference between the Y values at the end points of the interval, and ∆X is the length of the interval.

Y(7) = 3/7-2 = -11/7

Y(4) = 3/4-2 = -5/4

(∆Y)/(∆X) = (-11/7 - (-5/4))/(7 - 4) = (-9/28)/(3) = -3/28

______

Perhaps you intend y=3/(x-2). In that case, (∆y)/(∆x) = (3/5 - 3/2)/(7-4) = -3/10.

Y(7) = 3/7-2 = -11/7

Y(4) = 3/4-2 = -5/4

(∆Y)/(∆X) = (-11/7 - (-5/4))/(7 - 4) = (-9/28)/(3) = -3/28

______

Perhaps you intend y=3/(x-2). In that case, (∆y)/(∆x) = (3/5 - 3/2)/(7-4) = -3/10.